Conserved and Diverged Functions of the Calcineurin-Activated Prz1 Transcription Factor in Fission Yeast. Issue 4 (19th February 2016) - Chatfield-Reed, Kate; Vachon, Lianne; Kwon, Eun-Joo Gina; Chua, Gordon
Abstract: Gene regulation in response to intracellular calcium is mediated by the calcineurin-activated transcription factor Prz1 in the fission yeast Schizosaccharomyces pombe . Genome-wide studies of the Crz1 and CrzA fungal orthologs have uncovered numerous target genes involved in conserved and species-specific cellular processes. In contrast, very few target genes of Prz1 have been published. This article identifies an extensive list of genes using transcriptome and ChIP-chip analyses under inducing conditions of Prz1, including CaCl2 and tunicamycin treatment, as well as a ∆pmr1 genetic background. We identified 165 upregulated putative target genes of Prz1 in which the majority contained a calcium-dependent response element in their promoters, similar to that of the Saccharomyces cerevisiae ortholog Crz1 . These genes were functionally enriched for Crz1 -conserved processes such as cell-wall biosynthesis. Overexpression of prz1 + increased resistance to the cell-wall degradation enzyme zymolyase, likely from upregulation of the O -mannosyltransferase encoding gene omh1 + . Loss of omh1 + abrogates this phenotype. We uncovered a novel inhibitory role in flocculation for Prz1. Loss of prz1 + resulted in constitutive flocculation and upregulation of genes encoding the flocculins Gsf2 and Pfl3, as well as the transcription factor Cbf12. The constitutive flocculation of the ∆prz1 strain was abrogated by the loss of gsf2 + or cbf12 + . This study reveals that Prz1 functions as a positive and negative transcriptional regulator of genes involved in cell-wall biosynthesis and flocculation, respectively. Moreover, comparison of target genes between Crz1 /CrzA and Prz1 indicate some conservation in DNA-binding specificity, but also substantial rewiring of the calcineurin-mediated transcriptional regulatory network.